PERSEPSI PEMBACA TENTANG BERITA PEMBANGUNAN DI SURAT KABAR RADAR BOGOR (The Readers’ Perception on The Development News in Radar Bogor Newspaper) - Gusmia Arianti; Amiruddin Saleh; Wahyu Budi Priatna (Institut Pertanian Bogor, 2015)
ABSTRACT The existence of newspaper becomes one of the elements that can change the society's role in development, especially in agriculture and rural areas. Radar Bogor is a local newspaper that becomes the reference of information sources forthe community of Bogor. The purposes of the study were to analyze the characteristics of the readers, factors of the characteristics of the readers that have a relationship with the readers’ perception and influence of the readers’ perception on the elements of the development news in Radar Bogor Newspaper toward their behavioral changes. The sample selection method used in the study was Multiple Stage Sampling. The samples included 99 readers. The data analysis was carried out using the descriptive correlational analysis and SEM. The readers’ perception on the elements of development news has an influence on the changes of the readers’ behavior. Differences of influence on cognitive and affective changes occur because of the way readers obtain the newspaper. Changes in cognitive aspect based on the readers’ perception on the elements of the development news in Radar Bogor Newspaper are relatively stronger than their affective changes. Keywords: development news, newspapers, perception, readers’ behaviors, the elements of the development news